Radicals

Algebra Level 3

( 5 + 6 + 7 ) ( 5 + 6 7 ) ( 5 6 + 7 ) ( 5 + 6 + 7 ) = ? \large \left(\sqrt{5}+\sqrt{6}+\sqrt{7}\right)\left(\sqrt{5}+\sqrt{6}-\sqrt{7}\right)\left(\sqrt{5}-\sqrt{6}+\sqrt{7}\right) \left(-\sqrt {5} + \sqrt{6}+\sqrt{7}\right)=?


The answer is 104.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

2 solutions

X = ( 5 + 6 + 7 ) ( 5 + 6 7 ) ( 5 6 + 7 ) ( 5 + 6 + 7 ) Note that ( a + b ) ( a b ) = a 2 b 2 = ( ( 5 + 6 ) 2 7 ) ( 7 ( 6 5 ) 2 ) = 7 ( 6 + 5 ) 2 + 7 ( 6 5 ) 2 ( 6 + 5 ) 2 ( 6 5 ) 2 49 = 7 ( 2 ( 6 + 5 ) ) ( 1 ) 2 49 = 104 \begin{aligned} X & = \color{#3D99F6}\left(\sqrt 5 + \sqrt 6 + \sqrt 7\right) \left(\sqrt 5 + \sqrt 6 - \sqrt 7\right) \color{#D61F06} \left(\sqrt 5 - \sqrt 6 + \sqrt 7\right) \left(-\sqrt 5 + \sqrt 6 + \sqrt 7\right) & \small \color{#3D99F6} \text{Note that }(a+b)(a-b) = a^2-b^2 \\ & = \color{#3D99F6}\left((\sqrt 5 + \sqrt 6)^2 - 7\right) \color{#D61F06}\left(7 - (\sqrt 6 - \sqrt 5)^2 \right) \\ & = {\color{#3D99F6} 7 \left(\sqrt 6 + \sqrt 5 \right)^2 + 7 \left(\sqrt 6 - \sqrt 5 \right)^2} - \left(\sqrt 6 + \sqrt 5 \right)^2 \left(\sqrt 6 - \sqrt 5 \right)^2 - 49 \\ & = {\color{#3D99F6} 7 \left( 2 (6 +5) \right)} - \left(1 \right)^2 - 49 \\ & = \boxed{104} \end{aligned}

The product of the first and second term is ( 5 + 6 + 7 ) ( 5 + 6 7 ) = ( 5 + 6 ) 2 ( 7 ) 2 = 5 + 2 30 + 6 7 = 4 + 2 30 (\sqrt{5}+\sqrt{6}+\sqrt{7})(\sqrt{5}+\sqrt{6}-\sqrt{7})=(\sqrt{5}+\sqrt{6})^2-(\sqrt{7})^2=5+2\sqrt{30}+6-7=4+2\sqrt{30}

The product of the third and fourth term is

( 5 6 + 7 ) ( 5 + 6 + 7 ) = ( 7 + ( 5 6 ) ) ( 7 ( 5 6 ) = ( 7 ) 2 ( 5 6 ) 2 = 7 ( 5 2 30 + 6 ) = 4 + 2 30 (\sqrt{5}-\sqrt{6}+\sqrt{7})(-\sqrt{5}+\sqrt{6}+\sqrt{7})=(\sqrt{7}+(\sqrt{5}-\sqrt{6}))(\sqrt{7}-(\sqrt{5}-\sqrt{6})=(\sqrt{7})^2-(\sqrt{5}-\sqrt{6})^2=7-(5-2\sqrt{30}+6)=-4+2\sqrt{30}

The final product then is

( 4 + 2 30 ) ( 4 + 2 30 ) = 16 + 4 ( 30 ) = 104 (4+2\sqrt{30})(-4+2\sqrt{30})=-16+4(30)=104

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...